ANALISIS KADAR MERKURI PADA BIOTA AIR DENGAN NANOPARTIKEL PERAK SECARA CITRA DIGITAL DI LOKASI PENAMBANGAN EMAS KABUPATEN LEBONG - Hendry Nordan; Mochamad Lutfi Firdaus; Rina Elvia (ALOTROP, 2020)
This study aimed at determining of how the sensitivity of silver nanoparticles (NPP) in detecting metal mercury in aquatic biota samples through digital imagery. The Sampling of aquatic biota was carried out in the gold mining location of Lebong Tambang village in Lebong district (102 ° 12'00 "-102 ° 18'05" BT and 3 ° 10'00 "-3 ° 17 ' 00 "LS.) The aquatic biota samples analyzed included fish, shellfish, shrimp and plants as well as comparison samples such as water and sediment. The Analysis of mercury level was carried out from December 2018 - March 2019 by using NPP of digital imagery method. The digital imagery method was used as a detector to replace the conventional spectrophotometer. The result of mercury level in aquatic biota with NPP in digital imagery was susceptible compared to the UV-Vis spectrophotometry method. It can be seen from the Limit Of Detection (LOD) score of the digital imagery method with the SLR data analysis technique by using a digital camera that is equal to 2.305 ppb, where the score was smaller than the LOD value in spectrophotometry which is 300 ppb. The results of the analysis of mercury level by using digital imagery method were obtained the concentration on pool shells of 196.8 ppb, in pond fish samples of 155.7 ppb, in shrimp samples of 81.2 ppb, in river fish samples of 81.1 ppb, and in plant samples of 50.9 ppb. thus, these results indicate that the presence of mercury ions in the samples of aquatic biota tested has levels above the threshold, which means samples of fish, shrimp, shellfish and plants were risk to be consumed